It gets better coming out, overcoming bullying, and creating a life worth living - Savage, Dan; Miller, Terry (Dutton, 2011)
A collection of original essays and expanded testimonials written to teens from celebrities, political leaders, and everyday people. While many of these teens can't see a positive future for themselves, we can. We can show LGBT youth the kind of happiness, potential, and satisfaction their lives hold if they can just get through these early years.